Analysis of short circuit electromagnetic force of salient pole synchronous motor winding. Issue 4 (May 2020) - Shen, Yubo; Zhang, Dewen; Xu, Minhu; Kong, Fanrong; Zhang, Peng; Chen, Shiyu; Shang, Shulei; Zhao, Xiangyu
Abstract: China's pumped storage power station has a broad prospect, in which salient pole synchronous motor plays an important role. In this paper, the mathematical expression of electromagnetic force in the case of short circuit of the excitation winding of salient pole synchronous motor is derived, and the variation law of electromagnetic force density in the case of fault corresponding to the electromagnetic force of damping winding is calculated. The mathematical law of electromagnetic force in the case of short circuit fault of salient pole synchronous motor is revealed, which has practical reference significance.